Trade-Offs and Synergies Between Food and Fodder Production and Other Ecosystem Services in an Actively Restored Forest, Natural Forest and an Agroforestry System in Ghana - Damptey, Frederick Gyasi; de la Riva, Enrique G.; Birkhofer, Klaus (Frontiers in Forests and Global Change, 2021)
Active restoration of degraded areas with multi-purpose tree species has been proposed as a measure to counter the losses from deforestation and mitigate consequences for local human communities. Ecosystem Services (ES) proxies in an actively restored forest were compared to a local agroforestry system and a natural forest. The results provide information about trade-offs and synergies between proxies of multiple ES(s). ES proxies were assessed according to the following categories: a) food-tree ES: biomass of food and fodder trees, b) other trees ES: biomass of fuelwood, medicine or mulch trees, c) ES-providing arthropods: the number of detritivorous and predaceous arthropods, d) carbon storage and e) tree diversity. Eight replicated plots with sizes of 20 × 20m were established in each forest type and the following ES proxies were quantified: tree diversity was estimated as the taxonomic richness of all trees with a diameter at breast height ≥ 10 cm in each plot and further classified into ES categories. Ground-dwelling arthropods were sampled for ten weeks with five pitfall traps in each plot and categorized as decomposers and predators. ES proxies based on tree biomass were highest in the natural forest. Fodder, medicine, fuelwood and mulch ES proxies were significantly higher in the restored forest than in the agroforestry system. Decomposer arthropods were most dominant in the natural forest, followed by the restored forest and the agroforestry system. Predacious arthropods were more dominant in the restored forest than in the other forest types. Carbon storage was highest in the natural forest, followed by the agroforestry system and the restored forest. The actively restored forest took an intermediate position between the agroforestry system and the natural forest regarding values for all nine ES proxies. Out of the 14 possible relationships between food or fodder and other ES proxies, five were significantly positive (synergies) with no observed trade-offs (significant negative relationships). High fodder production in the restored and natural forests went along with higher values of other biomass ES proxies and numbers of beneficial arthropods, while higher food biomass also correlated positively with numbers of decomposing arthropods.